Low-Loss Waveguide Crossing for Complicated On-Chip Microwave Photonic Processor - Ziyang Lu; Jiachen Li; Hongwei Chen; Sigang Yang; Minghua Chen (IEEE Photonics Journal, 2024)
To realize large device density and high complexity in future on-chip microwave photonic system, a waveguide crossing with low loss, crosstalk and reflection is designed on the silicon nitride waveguide platform, which is compatible for on-chip microwave photonic processor. Furthermore, a multi-channel microwave photonic signal processing chip is fabricated based on the proposed waveguide crossings, and the performance of the chip is evaluated. In simulation, the proposed waveguide crossing maintains an insertion loss of ∼0.08 dB per crossing in the wavelength range of 1500 nm – 1600 nm, while the experiment result is 0.086 dB per crossing. As the wavelength changes, the measured variation of insertion loss per crossing is less than 0.02 dB. The crossings on the signal processing chip induce an extra insertion loss of 1.2 dB to each channel. Meanwhile, the measured crosstalk and reflection are both below −44 dB. Furthermore, the proposed waveguide crossing shows significant robustness for fabrication. With the advantages of ultra-low loss, crosstalk and reflection, the proposed waveguide crossing may support the establishment for future complicated on-chip microwave photonic systems.